The Importance of Time in Criminalistics - Fenyvesi, Csaba (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
Monographs and studies found in Hungarian academic literature on criminalistics cover numerous fields and aspects of the theory of this discipline. The focal point of this study stems from the fact that in the professional literature however, there is no writing about the time dimension of criminalistics. One of the seven basic questions from the author’s pyramid model, namely “when it happened” is a really important fact in all criminal cases for all parties, such as investigators, prosecutors, defence counsels and finally for the judges.